Peningkatan Kompetensi Manajemen Asfiksia Bayi Baru Lahir Melalui Metode Cooperative-Learning - Reni M. Kusuma; Anita D. Anwar; Dwi Prasetyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: The competence of asphyxia management on newborn baby is essential for midwife. The quality of learning process should be improved by applying interactive learning method. The cooperative learning method is often applied to enhance the effectiveness of clinical learning process. The purpose of this research was to analyze the influence of cooperative learning on competence which consists of student’s knowledge, attitude, and skill in comparison to teacher-centered learning method.Method: This is quasi-experimental research with control group pre-test and post-test design Samples were third semester students at Stikes A. Yani Yogyakarta. The samples were 80 students in cooperative learning group and 90 students in teacher-centered learning group.Result: The result showed that  there was an improvement of knowledge in cooperative learning group compared to teacher-centered learning group (p=0.002). The improvement od student’s attitude in cooperative learning group was significantly higher than teacher-centered learning group (p=0.001). In the field of skills, cooperative group, although not significant (p=0.671). The competence was significantly higher in cooperative learning group rather than in teacher-centered learning group (p=0.027). Correlation between competence and method of learning was weak (rpbi  = 0.134, p= 0.041).Conclusion: Cooperative learning method is proven to be improve student’s knowledge, attitude and skills. The difference is not significant for skills domain. Cooperative learning method is proven to improve student’s competence in carrying out the management of newborn babies asphyxia, even though the correlation is weak.